From formalism to intuition: probing the role of the trochee in German nominal plural forms in L1 and L2 German speakers - Schuhmann, Katharina S.; Smith, Laura Catharine (Frontiers in Language Sciences, 2024)
Accounting for plural formation in Standard German (SG) nominals has proven to be a challenging endeavor. Numerous formalisms and models have been proposed and intensely debated over the past decades. The fundamental challenge lies in the fact that German has a large number of suffix allomorphs, some of which can be used with or without stem-vowel fronting/raising (umlaut). Current research suggests that at the segmental level it is impossible to fully predict how plurality will be marked for a given singular form. At the suprasegmental level, however, the vast majority of German plurals, except plurals ending in <-s> /-s/, exhibit a specific prosodic shape word-finally: a strong-weak pattern, i.e., a sequence of a stressed syllable followed by an unstressed syllable. In other words, German plurals tend to end in a disyllabic trochee. Previous experimental investigations have sought to provide empirical evidence in favor of various formal models. To date, these experimental studies have focused primarily on the segmental make-up of plural suffixes. It remains untested – and thus largely unknown – whether the prosodic pattern at the interface between morphology and phonology is an active, productive part of the grammar of first language (L1) and second language (L2) users of German across four proficiency levels. We therefore set out to test whether users actively apply the trochaic principle in the production and comprehension of German plural nouns. To this end, we tested L1 and L1 English-L2 German users on a non-word production elicitation task, in which they produced plural forms for non-words, akin to a wug-test; L2 users additionally completed a plural elicitation task with existing German nouns. All users then participated in a grammatical acceptability judgment task, in which they rated German nouns with various incorrect and correct (i.e., SG) plural forms on a(n 8-point) Likert scale. Our data show that L2 learners produce more trochaic plural forms with increasing proficiency, and that more advanced speakers show a stronger correlation between their rating and plural forms that vary in correctness and prosody. We discuss how the data can be captured with various models of German plurals.